Assessing effectiveness and side effects of likely “seal safe” pinger sounds to ward off endangered franciscana dolphins (Pontoporia blainvillei) - Paitach, Renan L.; Amundin, Mats; Königson, Sara; Cremer, Marta J. (Marine mammal science, 2022)
The franciscana (Pontoporia blainvillei) is the most endangered dolphin in the western South Atlantic Ocean due to bycatch. Our goal was to test the efficiency of a likely “seal safe” pinger (Banana Pinger, Fishtek Marine Ltd.) to ward off franciscanas, as well as investigating possible side effects of habituation and habitat exclusion. We deployed the pinger within a grid of click detectors (C‐POD, Chelonia Ltd.) in Babitonga Bay, southern Brazil, and the narrow band high frequency sonar click trains were used as a proxy for presence of the franciscanas and response to the pinger. The presence of franciscanas next to the pinger and at 100 m away decreased by 19.4% and 15.4%, respectively, when the pinger was switched on, indicating that the franciscanas avoided the area of the pinger. This avoidance response could not be seen at 400 m away. No habituation effect was noted at any distance. There was a slight gradual decrease in detections over the course of the study at all distances, which is probably related to seasonal variation in the population's habitat use, but this requires attention in future studies. The likely “seal safe” pinger sounds effectively warded off franciscanas and thus has the potential to reduce bycatch.